Exposition and Application of a Framework for Integration in a Mixed Methods Study: A Case Study From Complicated Grief. (January 2022) - Dodd, Anne; Guerin, Suzanne; Delaney, Susan; Dodd, Philip
The methodological literature considers the challenges of integrating data from various sources. However, it is sparse on how such integration might be executed. The unique contribution of this article is that, exploring mental health professionals' attitude to complicated grief, it combines existing analysis principles and methods to present a stepwise framework that aims to guide the integration process. In a three-phase exploratory sequential mixed methods study (systematic review, qualitative, and quantitative research phases), the findings from the individual phases provided the data for integration, which involved data reduction, transformation using qualitization, and comparison through a process of following the thread. The article demonstrates how this method of integration produced added value, allowing identification of a more nuanced conclusion.